Effects of Accuracy Training for Individuals with Various Disabilities in Inclusive Game Baskin - Milošević, Živan (Specijalna edukacija i rehabilitacija, 2025)
Introduction. Numerous studies have indicated the positive effects of adapted sports programs on enhancing the sports skills of individuals with multiple forms of disabilities. Aim. The aim of this research was to examine the extent of changes over four time series in the aspect of accuracy in the inclusive sport of Baskin for individuals with physical and intellectual disabilities. Methods. Nine participants, four with motor disabilities and five with intellectual disabilities, with an average age of (28.92 ± 11.02), took part in this study. An accuracy assessment test was conducted from three positions from which players in the role of 2 can shoot in situational Baskin play. Results. No significant effect of the interaction between time and type of disability was found (Wilks’ lambda =.92), p=.93, F (3.5) = .14, partial eta squared = 0.08). The separate effect of the two types of disabilities was not significant (F (1. 7) = 1.304, p=.29, partial eta squared =.157), from which it can be concluded that there was no significant improvement either in the group of participants with intellectual disabilities or in the group of participants with motor disabilities. Conclusions. The results indicated that there were no statistically significant differences between the four measurements, nor were there statistically significant improvements between the groups of participants.